2016
DOI: 10.1002/pola.28114
|View full text |Cite
|
Sign up to set email alerts
|

Organic-acid mediated bulk polymerization of ε-caprolactam and its copolymerization with ε-caprolactone

Abstract: Polyamides (PA) constitute one of the most important classes of polymeric materials and have gained strong position in different areas, such as textiles, fibers, and construction materials. Whereas most PA are synthesized by step‐growth polycondensation, PA 6 is synthesized by ring opening polymerization (ROP) of ε‐caprolactam (ε‐CLa). The most popular ROP methods involve the use of alkaline metal catalyst difficult to handle at large scale. In this article, we propose the use of organic acids for the ROP of ε… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The products used for anionic ring opening polymerization of polyamide 6 (PA6) are the ε-caprolactam monomer, purchased from BASF (Rhein, Germany), sodium aluminum lactate, as initiator, and a commercial mixture of isocianates, as an activator [33,34,35,36]. The reinforcement fabrics used were glass fibers (GF) and carbon fibers (CF) fabrics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The products used for anionic ring opening polymerization of polyamide 6 (PA6) are the ε-caprolactam monomer, purchased from BASF (Rhein, Germany), sodium aluminum lactate, as initiator, and a commercial mixture of isocianates, as an activator [33,34,35,36]. The reinforcement fabrics used were glass fibers (GF) and carbon fibers (CF) fabrics.…”
Section: Methodsmentioning
confidence: 99%
“…The CAPROCAST process developed at TECNALIA [33,34,35,36] consists of a device for polymerizing lactams directly in a mold. In a pressurized vessel connected to the mold, the reaction mixture was prepared by melting the reactants at 125 °C under stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For poly(ε-caprolactam-co-ε-caprolactone) (P(CLA-co-CLO)), the current researches mainly focus on the synthesis and structure characterizations of copolymers. Many synthetic methods have been reported, such as anionic copolymerization, interfacial copolymerization, hydrolytic ring-opening polymerization, and polycondensation [7][8][9][10][11][12][13][14]. Regardless of the synthesis method and feeding sequence, the final products obtained are almost random or multiblock copolymers so far.…”
Section: Introductionmentioning
confidence: 99%
“…Deshayes and According to the DSC and WAXS results, Michell et al [5,9,[15][16][17] found that only the CLA sequence of P(CLA-co-CLO) copolymers could crystallize except for C 55 -ran-A 45 , and the crystallization temperature (T c ) shifts were affected by microstructure and the dilution effect due to the CLO interruptions. Sanchez et al [11] reported that only in the case of P(CLA 19 -co-CLO 81 ), both CLA and CLO sequences could crystallize, but only a single melting peak. Though the above works found both CLA and CLO sequence could crystallize through DSC melting curves, no extensive studies were carried out.…”
Section: Introductionmentioning
confidence: 99%